Development and validation of the facial scale (FaceSed) to evaluate sedation in horses - de Oliveira, Alice Rodrigues [UNESP]; Gozalo-Marcilla, Miguel; Ringer, Simone Katja; Schauvliege, Stijn; Fonseca, Mariana Werneck [UNESP]; Trindade, Pedro Henrique Esteves [UNESP]; Filho, José Nicolau Prospero Puoli [UNESP]; Luna, Stelio Pacca Loureiro [UNESP] (Public Library of Science (PLoS), 2021)
Although facial characteristics are used to estimate horse sedation, there are no studies measuring their reliability and validity. This randomised controlled, prospective, horizontal study aimed to validate a facial sedation scale for horses (FaceSed). Seven horses received detomidine infusion i.v. in low or high doses/rates alone (DL 2.5 μg/kg+6.25 μg/kg/h; DH 5 μg/kg+12.5 μg/kg/h) or combined with methadone (DLM and DHM, 0.2 mg/kg+0.05 mg/ kg/h) for 120 min, or acepromazine boli i.v. in low (ACPL 0.02 mg/kg) or high doses (ACPH 0.09 mg/kg). Horses' faces were photographed at i) baseline, ii) peak, iii) intermediate, and iv) end of sedation. After randomisation of moments and treatments, photos were sent to four evaluators to assess the FaceSed items (ear position, orbital opening, relaxation of the lower and upper lip) twice, within a one-month interval. The intraclass correlation coefficient of intra- and interobserver reliability of FaceSed scores were good to very good (0.74-0.94) and moderate to very good (0.57-0.87), respectively. Criterion validity based on Spearman correlation between the FaceSed versus the numerical rating scale and head height above the ground were 0.92 and -0.75, respectively. All items and the FaceSed total score showed responsiveness (construct validity). According to the principal component analysis all FaceSed items had load factors >0.50 at the first dimension. The high internal consistency (Cronbach´s α = 0.83) indicated good intercorrelation among items. Item-total Spearman correlation was adequate (rho 0.3-0.73), indicating homogeneity of the scale. All items showed sensitivity (0.82-0.97) to detect sedation, however only orbital opening (0.79) and upper lip relaxation (0.82) were specific to detect absence of sedation. The limitations were that the facial expression was performed using photos, which do not represent the facial movement and the horses were docile, which may have reduced specificity. The FaceSed is a valid and reliable tool to assess tranquilisation and sedation in horses.